Evaluación del tren de SUDS en el Parque Metropolitano San Cristóbal Sur (2017)
The objective of this document is to analyze the physical and chemical parameters of the input and output of a Sustainable Urban Drainage System (SUDS) installed in Parque Metropolitano San Cristóbal Sur, to determine the quality and quantity of water, to evaluate the performance of the system. At the same time, an analysis about the perspective and interaction of the community with this kind of system was made through surveys. This is a first approximation of the evaluation of SUDS in Bogota, and could be as reference for evaluations of future SUDS that will be installed in the city.